Pengembangan Bahan Ajar E-book Pada Materi Siklus Akuntansi Perusahaan Jasa Sebagai Pendukung Pembelajaran Saintifik Kelas X Akuntansi Di SMK Negeri 2 Tuban - Reynaldo Juniors; Joni Susilowibowo (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2020)
In the 2013 revised curriculum, teaching and learning activities require student to be more active in the learning process. In addition, teacher is required to have teaching materials that linked to technological advances that refer to basic competencies and scientific approach, adjusted for the student needs. This research aims to create a product in the form of an e-book for teaching materials and analyze the feasibility of e-book teaching materials about service company accounting cycle. This research used 4D model (define, design, develop and disseminate) that developed by Thiagarajan, Semmel, and Semmel, but this research is only carried out until the develop stage. The research instrument used by researchers in this article is an open poll which consists study sheet of media expert, graphic expert and linguist as well as enclosed that also consists validation sheet of media expert, graphic expert and linguist. The analysis technique used by the researcher consists of analysis of study sheets, which will be analyzed descriptively along with validation sheet analysis that will be analyzed using Likert scale as stipulation in the research provisions. The assessment results obtained from material expert by 89.51%, it has a splendid eligibility level. 92.66% from linguist and 96.01% from graphic expert are showing also a superior eligibility level. Thus, from the three components, it was obtained average of 92.72% with the splendid eligibility level. This research concludes that e-book, that has developed with a scientific approach, that contain service company accounting cycle material, is stated very worthy to be used in teaching learning activities.